Existentialism of Manto: Absurdity of Human Condition in 201C;Toba Tek Singh201D; and 201C;Khaled Mian201D; (Global Journal of Human-Social Science, 2019)
In this article I have attempted to re-read two of Sadat Hasan Manto s short stories Toba Tek Singh and Khaled Mian Both of these stories are examples of intense identity crisis alienation extreme existential angst which haunts the unique personalities of these stories Manto s stories have been often analysed from a post partitional perspective but some of these stories indeed exemplify existential features in the manner of the works of Sartre Camus and other thinkers and writers of the 20th century Europe The protagonist of these stories Bishen Singh and Mumtaz respectively depicts an uncompromising struggle of mankind against essentialised interpretations of their world and their attempt to resist it Manto s selection of unusual characters in these stories stretches the boundaries of existence and questions normative discourses of his sociopolitical environment
Keywords: existentialism; partition; saadat h323; asan manto; absurdism; essentialism; anxiety